Clinical outcome and cyclo‐oxygenase‐2 expression in five dogs with solar dermatitis/actinic keratosis treated with firocoxib. Issue 6 (15th October 2013) - Albanese, Francesco; Abramo, Francesca; Caporali, Chiara; Vichi, Gaia; Millanta, Francesca
<x xml:space="preserve">Abstract</x> Background The conversion of arachidonic acid into prostaglandin is catalysed by the cyclo‐oxygenases (COX‐1/COX‐2). Several studies indicate that COX‐2 is overexpressed in actinic keratosis in humans and dogs. Firocoxib is a COX‐2‐selective inhibitor that blocks the biochemical activity of COX‐2. Hypothesis/Objectives To evaluate the efficacy of firocoxib (5 mg/kg orally once daily) for the treatment of dogs with solar dermatitis/actinic keratosis. Methods Firocoxib 5 mg/kg was given orally once daily for 180 days to five dogs with clinical signs and histopathological lesions consistent with solar dermatitis/actinic keratosis. On days 0, 50 and 180, the severity of erythema, skin shine, induration and the number of comedones were evaluated by a clinical scoring system. On the same days, samples were collected for histopathology from 'target lesions' and COX‐2 expression was evaluated by immunohistochemistry. Results The clinical follow‐up showed that four of five dogs improved with the treatment; improvement in terms of histological findings was correlated with the regularization of the epidermal proliferation rather than the recovery of dermal changes. Conclusions and clinical importance A role for COX‐2 might thus be hypothesized in the pathogenesis of canine solar dermatitis.